COVID-19 vaccination produces exercise-responsive SARS-CoV-2 specific T-cells regardless of infection history - Kyle A. Smith; Tiffany M. Zúñiga; Forrest L. Baker; Helena Batatinha; Charles R. Pedlar; Shane C. Burgess; Michael P. Gustafson; Emmanuel Katsanis; Richard J. Simpson (Journal of Sport and Health Science, 2024)
Background: The mobilization and redistribution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) specific T-cells and neutralizing antibodies (nAbs) during exercise is purported to increase immune surveillance and protect against severe coronavirus disease 2019 (COVID-19). We sought to determine if COVID-19 vaccination would elicit exercise-responsive SARS-CoV-2 T-cells and transiently alter nAb titers. Methods: Eighteen healthy participants completed a 20-min bout of graded cycling exercise before and/or after receiving a COVID-19 vaccine. All major leukocyte subtypes were enumerated before, during, and after exercise by flow cytometry, and immune responses to SARS-CoV-2 were determined using whole blood peptide stimulation assays, T-cell receptor (TCR)-β sequencing, and SARS-CoV-2 nAb serology. Results: COVID-19 vaccination had no effect on the mobilization or egress of major leukocyte subsets in response to intensity-controlled graded exercise. However, non-infected participants had a significantly reduced mobilization of CD4+ and CD8+ naive T-cells, as well as CD4+ central memory T-cells, after vaccination (synthetic immunity group); this was not seen after vaccination in those with prior SARS-CoV-2 infection (hybrid immunity group). Acute exercise after vaccination robustly mobilized SARS-CoV-2 specific T-cells to blood in an intensity-dependent manner. Both groups mobilized T-cells that reacted to spike protein; however, only the hybrid immunity group mobilized T-cells that reacted to membrane and nucleocapsid antigens. nAbs increased significantly during exercise only in the hybrid immunity group. Conclusion: These data indicate that acute exercise mobilizes SARS-CoV-2 specific T-cells that recognize spike protein and increases the redistribution of nAbs in individuals with hybrid immunity.